ANALISIS KRITERIA KUALITAS VAPE BERDASARKAN PREFERENSI KONSUMEN DI KOTA BATAM - Muabdi S, Ais; Asmarawati, Citra Indah (Computer Science and Industrial Engineering, 2023)
This study was conducted to analyze differences in consumer preferences in determining the quality and attitudes of consumers towards vape attributes in the city of Batam. The research was conducted in Batam Kota sub-district in June 2023. The method in this study uses a survey method with interviews based on a list of questions on a questionnaire. The sample was determined by random sampling method with 168 samples. The analysis used in the research is Chi Square analysis and Fishbein Multi-attribute. Chi Square analysis shows that apart from the comparison between prices below three hundred thousand rupiahs and between three hundred thousand rupiahs to seven hundred and fifty thousand rupiahs there is a difference of 95% confidence level. This means that there are differences in consumer preferences on vape. Multi-attribute Fishbein analysis shows that there are three attributes that get good consideration and two attributes get sufficient consideration in determining the quality of vape. The order of vape attributes from the highest consideration to the lowest consideration in determining vape quality is the availability of spare parts, product design, battery life, brand and price.